TRIM37-mediated stabilization of PEX5 via monoubiquitination attenuates oxidative stress and demyelination in multiple sclerosis insights from EAE and LPC-induced experimental models - Lai Jiang; Yue Jin; Yujia Han; Jin Fu (PLoS ONE, 2025)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS), characterized by myelin damage and neurodegeneration. This study focuses on the role of the TRIM37-PEX5 axis in regulating oxidative stress in oligodendrocytes and myelin repair, exploring its potential as a novel therapeutic target for MS. Through bioinformatics analysis, TRIM37 was found to be significantly downregulated in MS patients. In vitro experiments demonstrated that overexpression TRIM37 could stabilize PEX5 protein via non-degradative monoubiquitination, thereby maintaining peroxisomal metabolic function, reducing oxidative stress levels, significantly decreasing apoptosis in both oligodendrocytes and neurons, and promoting the expression of myelin basic protein (MBP). Further mechanistic studies revealed that the TRIM37-PEX5 axis mitigates apoptosis in oligodendrocytes by regulating oxidative stress levels. in vivo experiments further confirmed the neurorestorative effects of TRIM37. In an experimental autoimmune encephalomyelitis (EAE) model, overexpression TRIM37 significantly suppressed neuroinflammation mediated by microglia, reduced the expression of interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α), and alleviated demyelination lesions (as evidenced by reduced myelin damage shown by Luxol fast blue (LFB) staining, P < 0.001), while simultaneously increasing MBP expression levels ( P < 0.001). In conclusion, targeting the TRIM37-PEX5 axis holds promise as a novel strategy for improving myelin damage and providing neuroprotection in MS, offering a theoretical basis for interventions in metabolism-oxidative stress-related diseases.